Journey towards a Caribbean broadband community : editorial (2013)
Presents brief note on the Broadband Infrastructure Inventory and Public Awareness in the Caribbean (BIIPAC) project, one of the strategies to accelerate the penetration rate and usage of broadbank services.
Permanently located in IIS.